Dynamic mechanical properties of continuously cast Al alloy in electromagnetic stirrer - Lee, Dock-Young; Kang, Suk-Won; Kim, Ki-Bae (TRANS TECH PUBLICATIONS LTD, 2006)
The mechanical properties of electromagnetically stirred billet of Al alloy during continuous casting such as a tensile, impact, and fatigue property was examined with respect to a size and roundness of primary a phase to examine the influence of the globularization and refining of primary alpha phase on the dynamic mechanical property. The billet was continuously cast in a casting speed of 100 to 600 mm/min during the electromagnetic stirring with a magnetic flux density of 700 Gauss and then was heat-treated. All tensile properties were enhanced with decreasing the size of primary alpha crystal and the ultimate tensile strength (UTS), yield strength, and elongation was obtained 320MPa, 235MPa, and 17.8%, respectively, at a size of primary a phase of 77 urn. The fatigue life at fracture was largely improved by 37% from 1.25 x 10(5) to 1.7 x 10(5) cycles and the fracture toughness was obtained approximately 7.25 joules as a maximum value at a minimum size of primary alpha phase on the present experiment condition. Therefore, it indicates that all mechanical properties can be improved at the higher casting speed owing to the fine microstructure of a primary alpha phase and also eutectic phase due to the higher cooling rate.
Keywords: BEHAVIOR